Advance Entity Liking with a Knowledge Base (International Journal of Engineering and Computer Science, 2018)
Entity linking is the task to link entity mentions in text with their corresponding   entities in a knowledge base. Potential applications include information extraction, information retrieval, and knowledge base population. However, this task is challenging due to name variations and entity ambiguity. The large number of web applications generate knowledge base data which lead to major entity linking research. We present the overview of analysis and main approach to extract data from the raw data and liking the entities with context.